62‐2: Deep‐Red and Near‐Infrared OLEDs with High Efficiency and Long Lifetime for Display and Light‐Source Applications. Issue 1 (25th September 2020) - Seo, Satoshi; Tomida, Airi; Watabe, Takeyoshi; Kawano, Yuta; yamaguchi, Tomoya; Tominaga, Tetsuaki; Inoue, Hideko; Ohsawa, Nobuharu; Yamazaki, Shunpei
Abstract : A deep‐red OLED satisfying the BT.2020 standard achieved an extremely high external quantum efficiency (EQE) over 30% and long lifetime. Furthermore, a near‐infrared OLED with an emission peak around 800 nm, a maximum EQE of 7.2%, and less degradation was demonstrated. This efficiency is the best among reported near‐infrared OLEDs.